Odpowiedzi

Najlepsza Odpowiedź!
2010-01-16T15:10:13+01:00
1.
g) 3x²y × (-⅙ xy)= 3x(do4) y(do potęgi 2) (nie wiem co to jest ⅙ )
h) -3 (-x) × (-x) × (-y) = -3x(do szescianu) *-y
i) 0,2tsts² × (-15) = 0,2*-15 *s(do szescianu) *t(do kwadratu) * x

2.

b)-2t, -st= 2st(kwadrat)
c)-5b, -st=5bst
d)pr, 2pr=2p(kwadrat)r(kwadrat)
e)-x, -x²=x(do szescianu)
f)½ ab, -⅙ a²= ( nie wiem przez ten znak ⅙)
1 3 1
2010-01-16T15:28:52+01:00
1. 3x(do4) y² (nie wiem co to jest ⅙ )
-3x(do sześcianu) • -y
0,2• -15 •s(do sześcianu)•t² • x

5. 2st(kwadrat)
5bst
2p²r²
x(do sześcianu)
( nie wiem przez ten znak ⅙)
1 2 1